Índice de masa corporal, riesgo cardiovascular y prevalencia de los trastornos de conducta alimentaria en adolescentes de la I.E.P.I.P.S.M. San Martín de Porres, Iquitos – 2024 - Guerra Guerra, Margaret Abigail (2025)
The objective of this study was to determine the relationship between the prevalence of eating disorders and body mass index and cardiovascular risk in adolescents from the I.E.P.I.P.S.M. San Martin de Porres in the district of Iquitos. The study was descriptive and correlational, non-experimental and quantitative, cross-sectional. The sample consisted of 205 schoolchildren aged 15 to 17 years of both sexes. Weight, height, abdominal circumference and blood pressure measurements were taken, in addition to a questionnaire to measure the risk of the prevalence of eating disorders. 60.49% had a normal body mass index, 27.80% were overweight, 9.76% were obese and 1.95% were thin. 73.66% had low cardiovascular risk, 23.41% had high risk and 2.93% had very high risk. 73.17% of adolescents had normal blood pressure, 23.41% had prehypertension, and 3.41% had hypertension. The diet indicator showed 36.59% of adolescents at risk and 63.41% without risk. The Bulimia indicator showed 14.63% at risk and 85.37% without risk. The oral control indicator showed 43.41% at risk and 56.59% without risk in the adolescents evaluated. The adolescents evaluated presented 27.80% at risk for eating disorders and 72.70% without risk for TCA. A statistical relationship was found between eating disorders and body mass index and cardiovascular risk, however, no statistical relationship was found between Bulimia and abdominal perimeter and blood pressure.